Exploring the influence of project complexity on the mega construction project success: a qualitative comparative analysis (QCA) method. Issue 9 (5th May 2020) - Ma, Li; Fu, Hongwei
Abstract : Purpose: Understanding the impact of project complexity on the mega construction project success will help improve the efficiency of project management. However, the influencing mechanism of project complexity on project success has not been clearly depicted. This paper aims to divide project complexity and project success into five dimensions, trying to explore the impact of different complexity combinations on mega construction project success. Design/methodology/approach: This study applies the qualitative comparative analysis (QCA) method to find out the impact of the combinations of different project complexities on the every dimension of mega construction project success. First, 21 cases were interviewed and scored in five categories of project complexities and five aspects of project success. Second, with the QCA program, the combinations of different project complexities influencing every aspect of mega construction project success was obtained. Findings: This research found that high organizational complexity or a combination of high environmental complexity and goal complexity can lead to serious schedule delays of mega construction projects, high technological complexity and goal complexity are important reasons for cost overrun, high technological complexity or a combination of high environmental complexity and low organizational complexity usually lead to low quality of mega construction projects, high goal complexity and cultural complexity are important factors affecting the key stakeholders' satisfaction and high technological complexity and environmental complexity are the reasons for the poor sustainability of mega construction projects. Originality/value: This study clearly reveals the influencing mechanism of project complexity on mega construction project success, which can help the project managers to understand and assess the complexity of mega construction projects and accurately predict their negative impacts on the mega construction projects.